Classical Guidance Materials in Social Affairs in Class VII of Middle School Students - Pratiwi, Tina; Farozin, Muh. (International Journal of Psychosocial Rehabilitation, 2020)
Social guidance delivered through classical guidance is an important thing to consider to be able to avoid students from delinquency or deviations in the social field. Even so, there is still limited material that is appropriate and by the needs of students that can be used as a reference or basis by the Guidance and Counseling teacher in providing classical social sector guidance to SMPN students. The purpose of this study is to find the right material and as needed for classical guidance in the social field of SMPN students. The sample in this study amounted to 353 from 14 public high schools throughout Yogyakarta which were conducted on February 4, 2019 - March 1, 2019. The instrument used was a questionnaire about INATBKBS. The results revealed that of the 98 INATBKBS questionnaires there were 10 materials in the questionnaire needed and were suitable for making classical social guidance material, these 10 topics were the basis of material and references that could be used and developed by counseling guidance teachers in delivering social guidance through classical guidance in SMPN children for the next semester.